Formulasi dan Uji Aktivitas Antioksidan Sediaan Gel Ekstrak Etanol 70% Bawang Putih Tunggal (Allium sativum L.) - Ambarwati , Nadya; Nabillah Zahro, Syarifah; Rahayu , Asti (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Single garlic (Allium sativum L.) contains higher bioactive compounds compared to regular garlic. Some of them are organosulfur compounds that give a distinctive aroma and polyphenol compounds as antioxidants. This study aims to formulate a single garlic extract in a gel preparation that can prevent irritation and increase comfort when applied. This study aimed to determine the physicochemical characteristics, including organoleptic properties, pH, viscosity, spreadability, particle size, and antioxidant activity using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method. The results of the physicochemical characteristics test include the organoleptic test, which has a clear yellow gel texture with a distinctive odor of garlic, pH test on F1, F2, and F3, namely (4.70; 5.07; 5.10), viscosity is (9925.3; 9925.3; 9925 mPas), the spreadability test has met the requirements, and the particle size is (194.23; 206.19; 1751.495 nm). The IC50 values for F1, F2, and F3 gel preparations were 128.2451 ppm, 110.279 ppm, and 89.2796 ppm, respectively, indicating moderate antioxidant activity for F1 and F2, and strong antioxidant activity for F3. It can be concluded that the three gel preparations have met the requirements of the physicochemical characteristics test, then statistically analyzed using the OneWay ANOVA method so that it shows the effect of the amount of single garlic extract concentration on the three gel preparations. The IC50 results of the three gel preparations were analyzed by Paired T-test, showing the effect of the amount of concentration of a single garlic extract as evidenced by a sig value of 0.012 <0.05.